Critical thinking skills toward YouTube resources in students' argumentative texts - Wijaya, Andik Nur; Roki'ah, Siti (Englisia Journal, 2020)
This study explored critical thinking skills toward YouTube resources in students' argumentative texts. The study was conducted at two non-English majors of the universities in the Indonesian context. The data were in the argumentative forms that were constructed by selected students. This study used a content analysis approach that was involved in coding and categorizing to analyze the data. After the data were analyzed, the findings showed that the patterns of critical thinking elements of the student's argumentative texts were varied, and the integration of technology resources was able to foster critical thinking skills. However, it is based upon the quality of the technology itself and the instruction in the classroom. Thus, technology implementation, YouTube resources should be found on the quality of the resources and teaching in the school.